Housing and health: an updated glossary. Issue 9 (27th June 2022) - Mansour, Adelle; Bentley, Rebecca; Baker, Emma; Li, Ang; Martino, Erika; Clair, Amy; Daniel, Lyrian; Mishra, Shiva Raj; Howard, Natasha J; Phibbs, Peter; Jacobs, David E; Beer, Andrew; et al.
Abstract : Recent crises have underscored the importance that housing has in sustaining good health and, equally, its potential to harm health. Considering this and building on Howden-Chapman's early glossary of housing and health and the WHO Housing and Health Guidelines, this paper introduces a range of housing and health-related terms, reflecting almost 20 years of development in the field. It defines key concepts currently used in research, policy and practice to describe housing in relation to health and health inequalities. Definitions are organised by three overarching aspects of housing: affordability (including housing affordability stress (HAS) and fuel poverty), suitability (including condition, accessibility and sustainable housing) and security (including precarious housing and homelessness). Each of these inter-related aspects of housing can be either protective of, or detrimental to, health. This glossary broadens our understanding of the relationship between housing and health to further promote interdisciplinarity and strengthen the nexus between these fields.